2020
DOI: 10.1176/appi.ps.201900174
|View full text |Cite|
|
Sign up to set email alerts
|

Merging Intentional Peer Support and Dialogic Practice: Implementation Lessons From Parachute NYC

Abstract: This ethnographically informed implementation analysis of Parachute NYC between 2012 and 2015 documents the obstacles that can impede disruptive innovations in public mental health. Parachute combined family-based dialogic practice with peer-staffed crisis respite centers and mixed teams of clinicians and peers in an ambitious effort to revamp responses to psychiatric crises. This Open Forum reviews the demands posed by formidable contextual constraints, extended trainings in novel therapeutic techniques, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 8 publications
2
23
1
2
Order By: Relevance
“…Olson et al (2014) presented 12 fi delity criteria for practicing OD. Unlike fi ndings from the Collaborative Network Approach (CNA) study and Parachute projects, in which the authors pointed to a resistance of the OD model to fi delity criteria and standardization (Florence et al, 2020;Hopper et al, 2020), participants in our study found the 12 fi delity criteria to be helpful elements in the training program. Together with the key markers developed by Eiterå et al (2014), these "manuals" helped participants get a grip on the OD approach.…”
Section: Developing An Od Training Programcontrasting
confidence: 93%
See 2 more Smart Citations
“…Olson et al (2014) presented 12 fi delity criteria for practicing OD. Unlike fi ndings from the Collaborative Network Approach (CNA) study and Parachute projects, in which the authors pointed to a resistance of the OD model to fi delity criteria and standardization (Florence et al, 2020;Hopper et al, 2020), participants in our study found the 12 fi delity criteria to be helpful elements in the training program. Together with the key markers developed by Eiterå et al (2014), these "manuals" helped participants get a grip on the OD approach.…”
Section: Developing An Od Training Programcontrasting
confidence: 93%
“…According to Buus et al (2017), most of the fi delity criteria constructed for OD were not designed in such a way that they could be used in standardized measurements. Seikkula and Arnkil (2013) point out that context is an important factor in research studies, as does the CNA study (Florence et al, 2020) and the Parachute project (Hopper et al, 2020). Implementation science in general shows that implementation projects are most effective when tailoring a program fi t for the exact context (Flottorp & Aakhus, 2013).…”
Section: Developing An Od Training Programmentioning
confidence: 99%
See 1 more Smart Citation
“…Jedes der eingeschlossenen CR beschreibt eigene Ziele und Werte, worunter sich einige an der Definition der National Coalition for Mental Health Recovery (NCMHR) orientieren, die in den USA die Implementierung von CR vorantreibt [19]. Häufig wird das Ziel benannt, die Inanspruchnahme von psychiatrischen Rettungsstellen und Krankenhäusern und damit verbundene Belastungen, lange Behandlungsverläufe sowie teilweise auch Kosten zu reduzieren [6,10,[20][21][22]. Einige CR sind strukturell in das Versorgungssystem eingebettet.…”
Section: Ziele Werte Und Selbstverständnisunclassified
“…4 online); in 3 von 10 Projekten erfolgen Trainings für Intentional Peer Support (IPS). Einzelne CR richten ihre Arbeit an Konzepten des Need Adapted Treatment (NAT) oder des Wellness Recovery Action Plans (WRAP) aus [21,28].…”
Section: Mitarbeitende Und Trainingsunclassified